IMPLEMENTASI AI DALAM MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SI ERA SOSIETY 5.0 - Sutrisno, Tri (AZKIYA, 2025)
The objectives of this study is to explore the use of ChatGPT, a form of Artificial Intelligence (AI), as a learning medium in Islamic Religious Education (IRE) with regard to the fostering of independent learning among students in the Society 5.0 era. The research utilized a qualitative-descriptive approach focusing on library research by analyzing various literatures about the role of ChatGPT in education, particularly in IRE. The data was obtained through document analysis of books and scholarly journals such as other relevant research articles. The findings show that ChatGPT has potential in facilitating students’ autonomous interaction, flexibility of access, and adaptability of contextual Islam content to enhance learning independence. The results of this study suggest that utilizing ChatGPT as a learning tool can contribute to the digital evolution of religious education towards independence and sustainability.